Моделирование технологии изготовления субмикронных КМОП СБИС с помощью систем TCAD - Glushko, A. A.; Rodionov, I. A.; Makarchuk, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The features of technological processes for fabricating submicron CMOS VLSI circuits and their simulation are considered. Particular attention is given to modeling of the doping profile. Simulation of technological processes for submicron VLSI fabrication significantly reduces the cost of experimental work required for optimizing the design of device elements, especially impurity profiles.